Creative evaluation: A Constellation of Approaches toward the Future of Academic Integrity - Seeland, Josh; Rexe, Scout; Munn, Caitlin (Canadian Perspectives on Academic Integrity, 2023)
With academic integrity anchored in teaching and learning (Bertram Gallant, 2016), perhaps its future could be positively influenced by more creative evaluation processes and methods. In this interactive presentation, members of Assiniboine Community College’s (ACC) Learning Commons share the value of designing and developing creative evaluations which maintain academic integrity in the evaluation process and align to college standards. With omnipresent concerns about academic misconduct spanning higher education, course and assessment design remain a way to prevent and reduce its occurrence through already established pedagogical strategies. The multidisciplinary team of ACC’s Library Manager, Education Quality Assurance Specialist, and Instructional Designer will facilitate an exploration of creative evaluation that can be achieved by using a constellation of approaches. This exploration is based primarily on the works of creative evaluation from Christou et al. (2021) and assessment for inclusion by Tai et al. (2022). Participants will leave with an understanding of what creative evaluations are and look like, and how to move towards designing and developing them at their own institutions.